Constructing Mutually Unbiased Bases from Unextendible Maximally Entangled Bases. Issue 1 (February 2020) - Zhao, Hui; Zhang, Lin; Fei, Shao-Ming; Jing, Naihuan
Abstract : We study mutually unbiased bases (MUBs) in which all the bases are unextendible maximally entangled ones. We first present a necessary and sufficient condition of constructing a pair of MUBs in C 2 ⊗ C 4 . Based on this condition, an analytical and necessary condition for constructing MUBs is given. Moreover we illustrate our approach by some detailed examples in C 2 ⊗ C 4 . The results are generalized to C 2 ⊗ C d   ( d ≥ 3 ) and a concrete example in C 2 ⊗ C 8 is given.